Analysis of the effects of curcumin and symbiotic consumption on bones of rats submitted to the use of dexamethasone - de Oliveira, Julia Aparecida Galdino Torralba; Neves, Mariana Daudt; Sampaio, Gleicy Fernanda Soares; Constantino, Carlos José Leopoldo [UNESP]; Nakagaki, Wilson Romero (Elsevier, 2022)
Aims: Glucocorticoids have adverse side effects that can compromise bone tissue. There is evidence to show that symbiotics and curcumin can prevent bone loss. The aim of this study was to analyze the effects of curcumin and symbiotic to prevent and/or minimize a possible bone impairment in rats submitted to the use of dexamethasone. Methods: Fifty Wistar female rats were divided into five groups: control group (CT), dexamethasone control group (D), dexamethasone and symbiotic group (DS), dexamethasone and curcumin group (DC), and dexamethasone and symbiotic/curcumin group (DSC). Dexamethasone was applied three times a week, while the symbiotic and curcumin were administered daily. Alkaline phosphatase and calcium dosages, analysis of structural and material properties, and Raman analysis of femurs were performed. Key findings: Alkaline phosphatase was higher in the DC group. Maximum load and structural stiffness were higher in the CT group. Maximum stress was lower and similar between dexamethasone groups. The CT group had a lower percentage of strain, the D group had greater deformation compared to the DC group and the DS group presented more deformation than the DC group. The D, DS, and DSC groups had a lower elastic modulus compared to the CT group. The 960/1660 ratios of the D, DS, and DSC groups were different from the CT group. The 1070/1660 ratio was higher in the DC group. Significance: It was possible to verify that curcumin showed promising effects related to the increase in bone strength and mineralization, mitigating the deleterious effects caused by dexamethasone, when used simultaneously with this drug.
Keywords: Bone; Curcumin; Dexamethasone; Glucocorticoid; Symbiotic